Analysis of the full stress tensor in a micropillar: Ability of and difficulties arising during synchrotron based μLaue diffraction. (15th October 2016) - Davydok, Anton; Jaya, Balila Nagamani; Robach, Odile; Ulrich, Olivier; Micha, Jean-Sébastien; Kirchlechner, Christoph
Abstract: The full strain tensor present in a 2 · 2 · 6 μm 3 sized germanium micro pillar was measured by X-ray microdiffraction Laue during in situ loading. Initial orientation gradients, residual strains and diffraction peak streaking were found negligible. The obtained strain values from Laue pattern analysis have been used to calculate the deviatoric stress tensor. The collected patterns show a pillar rotation and a build-up of shear stress components acting parallel to the contact surface of the flat punch, which is both an indication for misalignment of the sample and counter-body during loading. Based on the assumption of stress free pillar-side faces the full stress tensor was further evaluated. The stresses acting in loading direction derived from the Laue patterns compared to engineering stresses calculated from the continuously recorded signal of the load cell are in agreement within 9%. The discrepancy is explained by the initial experimental misalignment of the pillar with respect to the counter-body. Finally, difficulties arising during such an in situ experiment are discussed. Graphical abstract: Highlights: Analysis of all deviatoric strain (stress) components in a micron sized pillar during in situ micro-compression Calculation of the full stress tensor by the assumption of stress free pillar surfaces Comparison of stress component in loading direction with the engineering stresses derived from the load cell